2003
DOI: 10.1089/154099903765448862
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Health-Related Quality of Life in Postmenopausal Women with Coronary Heart Disease: The Estrogen Replacement and Atherosclerosis (ERA) Trial

Abstract: These data suggest that both clinical status variables (particularly chest pain) and the psychosocial context (represented by dimensions of relationship quality) influenced HRQL in this cohort. Thus, interventions that combine medical treatments with psychosocially based interventions may be most effective for women at risk for impaired HRQL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…One study used SF‐36 to measure HRQoL and found low HRQoL scores, highlighting the failure to return to premorbid status . It reported lower Mental and Physical Component Summary scores among CHD patients compared with the healthy population .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used SF‐36 to measure HRQoL and found low HRQoL scores, highlighting the failure to return to premorbid status . It reported lower Mental and Physical Component Summary scores among CHD patients compared with the healthy population .…”
Section: Resultsmentioning
confidence: 99%
“…One study used SF‐36 to measure HRQoL and found low HRQoL scores, highlighting the failure to return to premorbid status . It reported lower Mental and Physical Component Summary scores among CHD patients compared with the healthy population . The reliability of these findings was further supported when Wang and colleagues used both a disease‐specific instrument (MIDAS) and a generic questionnaire (SF‐36), obtaining poor HRQoL scores from both instruments.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34][35] In a Swedish study conducted from 1989 to 1991, 413 patients with an acute MI were compared with 88 population controls. 32 Patients with acute MI perceived their health status as worse 1 month and 1 year after their event.…”
Section: Hrqol and Chdmentioning
confidence: 99%
“…34 On the other hand, among 301 US women in the Estrogen Replacement and Atherosclerosis (ERA) trial, a previous MI did not significantly predict scores of either the Physical Component Summary or Mental Component Summary of the SF-36. 33 …”
Section: Hrqol and Chdmentioning
confidence: 99%
“…Previous studies have reported negative correlates of QOL in individuals with heart disease including younger age, being unmarried, being unemployed, and having comorbid medical conditions [4][5][6][7][8][9][10]. However, prior studies have had limited sample sizes and primarily consisted of white, middle-aged male patients, despite the fact that coronary heart disease (CHD) is the leading cause of death and premature disability among women in the nation and that CHD disproportionately afflicts ethnic minorities [11].…”
Section: Introductionmentioning
confidence: 99%